Sustaining behavioural change: the power of positive emotions - Samanthika Gallage, H. P.; Heath, Teresa; Tynan, Caroline (Association for Consumer Research, 2017)
This study explores emotions experienced by consumers who give up excessive drinking and considers how these emotions help consumers to sustain their healthy consumption behaviours. Current studies mostly focus on changing risky consumption behaviours (excessive drinking, smoking and gambling), rather than sustaining the positive behavioural change, which is a key challenge for consumers (Peattie and Peattie 2009; Scammon et al. 2011). Negative emotional appeals such as guilt and fear have been widely used to discourage these unhealthy consumption behaviours (Antonetti, Baines, and Walker 2015; De Hoog, Stroebe, and de Wit 2007). However, negative emotional appeals can encourage maladaptive responses that could be damaging for healthy behaviour (Hastings, Stead, and Webb 2004) and some authors urge the use of positive emotions such as hope, love, and excitement to sustain a behavioural change (Peter and Honea 2012). Yet, we know little about positive emotions experienced by consumers who transit from a risky behaviour to a less risky behaviour (Fry 2014) and how these emotions may help them to sustain this change. As this study demonstrates, these emotions can be fundamental in the process of achieving and sustaining responsible drinking behaviour.